Constitutionality of Personal Laws and Movement Towards Uniform Civil Code in India - Panadan, Davis (2015)
The Personal Laws based on religion have created confusion and conflict and many of provisions in some of the Personal Laws are discriminatory and are against the basic human rights and fundamental equality enshrined in the Indian Constitution. The demand for a Uniform Civil Code has been raised right from the beginning of Indian Independence and the demand is getting wider support now especially among the educated segment of the population. The paper deals with the constitutionality of Personal Laws. So the question arises that whether Personal Laws come under the purview of Indian Constitution or whether Personal Laws are constitutionally valid is analysed in detail, the movement towards Uniform Civil Code are discussed and Uniform Civil Code with its pros and cons are looked into. The paper concludes with certain practical suggestions.
Keywords: Constitutionality; Fundamental Right; Human Right; Personal Laws; Secularism; Uniform Civil Code